A systematic review of community participation measures for people with intellectual disabilities. Issue 3 (28th January 2019) - Taylor‐Roberts, Laura; Strohmaier, Sarah; Jones, Fergal; Baker, Peter
Abstract: Background: Community participation is considered a fundamental aspect of quality of life and one of the essential goals of services for people with intellectual disabilities, yet there is no agreed way of measuring community participation. Method: Two systematic searches were performed across eight electronic databases to identify measures of community participation and identify validation studies for each measure. Measures were included if they were developed for adults with intellectual disability, measured extent of participation and had published information regarding content and psychometric properties. Each measure was evaluated on the basis of psychometric properties and in relation to coverage of nine domains of community participation from the International Classification of Functioning, Disability and Health (ICF). Results: Eleven measures were selected with the quality rating scores varying substantially ranging from 2 to 11 of a possible 16. Conclusions: The majority of measures were not sufficiently psychometrically tested. Findings suggest a need for the development of a psychometrically robust instrument.